Differences in cause of death and age at death between people with and without diabetes over 10 years (2010–2020): A cross‐sectional study in Japan - Hirofumi Sugimoto; Noriko Ihana‐Sugiyama; Takehiro Sugiyama; Noriko Kodani; Ryotaro Bouchi; Mitsuru Ohsugi; Kohjiro Ueki; Hiroshi Kajio (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction Investigating the causes of death in individuals with diabetes compared with those without is essential for understanding diabetes care. However, methods for identifying individuals with diabetes within populations vary. We conducted a comparison of these groups under identical conditions, analyzing differences in causes and age at death, and assessing how different identification methods influence these outcomes. Materials and Methods This study used the clinical records of inpatients who died at the National Center for Global Health and Medicine from September 1, 2010, to December 31, 2020. Individuals with or without diabetes were defined using prescriptions and laboratory data. The cause of death was determined by the name of the primary illness provided by the attending physician at the time of death. Individuals with diabetes were stratified by different definitions, and their age at death was compared. Results In Individuals with diabetes, males accounted for 67.6%, and in those without diabetes, 57.0%. The mean age at death was 75.0 ± 11.8 and 73.8 ± 16.0 years, respectively. Malignant neoplasia was the most common cause of death in both groups, with a higher frequency in individuals with diabetes (36.9% vs 31.0%). Age at death of individuals with diabetes differed by up to 1.5 years, depending on the definitions. Conclusions Direct comparisons suggested that malignant neoplasia was the leading cause of death, and individuals with diabetes had a higher mean age at death. The method used to identify diabetes influenced these outcomes, emphasizing the importance of careful consideration in mortality studies.